Acceptability of employment readiness measures in youth and young adults on the autism spectrum: a mixed-methods study. Issue 16 (31st July 2022) - Wittevrongel, Krystle; Mitchell, Wendy; Hébert, Michèle L.; Nicholas, David B.; Zwicker, Jennifer D.
Abstract: Purpose: Reliable, valid, and pragmatic measures are essential for monitoring and evaluating employment readiness and comparing the effectiveness of alternative implementation strategies. The Work Readiness Inventory (WRI) and Ansell–Casey Life Skills Assessment (ACLSA) are valid measures of employment readiness in neurotypical populations; however, their acceptability (i.e., user perception of measure as agreeable/satisfactory) for persons on the autism spectrum is not yet known. This investigation assesses the acceptability of the WRI and a modified ACLSA (ACLSA-M) in measuring employment readiness in youth/young adults on the spectrum. Methods: A concurrent triangulation mixed-methods study design utilizing quantitative pre-post measurement of a community-based employment readiness program alongside qualitative survey assessment was employed to determine concurrent acceptability. For robustness, further explication through peer debriefing of experts evaluated the retrospective acceptability via interview and acceptability-rate assessment. Results: Findings indicated that both measures are acceptable, although individual- and job-specific item modifications are advised, particularly due to disability-specific needs. Significant change in employment readiness in youth/young adults on the spectrum supports concurrent acceptability. Peer debriefing provided rich data on retrospective acceptability. Acceptability-rates of 0.84 and 0.91 confirm broad acceptability of these measures. Conclusions: Implications are presented for clinicians and researchers, highlighting the relevance for autism-specific measurement development and acceptability. Implications for rehabilitation: Given the lower labor force participation of persons on the autism spectrum, a combination of measures should be used in the assessment of an individual's employment readiness. In youth and young adults on the spectrum, employment readiness can be measured using the Work Readiness Inventory (WRI) and a modified version of the Ansell–Casey Life Skills Assessment (ACLSA-M). In clinical practice and research, modifying the contents of these measures may be advised to minimize language complexity, and maximize ease in self report. When designing, developing, and testing new measures in rehabilitation practice or research, the intent should be broadened by involving diverse representation from the project outset, by engaging both those on the spectrum and neurotypical populations.